A reagent for heteroatom borylation, including iron mediated reductive deoxygenation of nitrate yielding a dinitrosyl complex. Issue 5 (20th January 2020) - Beagan, Daniel M.; Carta, Veronica; Caulton, Kenneth G.
Abstract : Borylated heterocycles are shown to be potent reductants towards organic substrates, as well as capable of nitrate deoxygenation. Abstract : 4, 4′-Bipyridyl is shown to be a catalyst for transfer of pinacolboryl groups from (Bpin)2 to nitrogen heterocycles and to Me3 SiN3 . Using stoichiometric (Bpin)2 (pyrazine) or (Bpin)2 (bipyridine) in an analogous manner, an aromatic nitro group is deoxygenated and subsequently borylated, and four-fold deoxygenation of (DIM)Fe(NO3 )2 (MeCN) to yield the dinitrosyl complex (DIM)Fe(NO)2 is facile. The co-product O(Bpin)2 is the quantitative fate of the removed oxo groups. With borylation of both nitrogen heterocycles and doubly deoxygenating two nitrates coordinated to a single metal center, broad spectrum methodology is demonstrated.